Tinjauan Hukum Pidana Islam terhadap Peraturan Daerah tentang Pengawasan dan Pengendalian Minuman Beralkohol di Kabupaten Madiun - Yuanita Sholikhah (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2020)
This study aims to determine the background and content of the District Regulation of Madiun No. 8 of 2006 concerning the Supervision and Control of Alcoholic Beverages, as well as the view of Islamic criminal law about the District Regulation. The results of the study concluded that the increasingly widespread circulation of liquor in the district of Madiun and the absence of regulations that prohibit the liquor became the reason for the enactment of Regional Regulation No. Madiun. 8 of 2006. It contains rules on prohibitions and legal sanctions against the consumption and distribution of alcoholic drinks, particularly of class B and C. Regarding the prohibitions contained in the Perda, it against Islamic criminal law due to government policies that still allow the circulation of alcoholic beverages even with very low levels. On the other hand, from the punishment aspect, the sanctions given are under the provisions of Islamic criminal law, because with the sanction it can provide lessons for deterrent and not repeat it.